(untitled) (Praxis Educativa, 2012)
Some of us who work at public universities in management posts have a story mainly characterised by teaching, research and extracurricular activities. Engaging in management is carried out by participating in groups chosen for those functions. Many a time, professional training and previous work are not specific enough to accomplish these complex tasks. As to Academic Management, complexities increase due to difficulties in outlining goals and topics that belong to this field in which different actors, scopes and dimensions are involved. This paper results from having worked as Academic Secretary at UNER and from my professional training in pedagogy, specifically in Educational Evaluation. It is my intention to visualize and discuss some issues concerning concepts and practices related to three main features: academic management, institutional policy and public university. I also intend to consider the difficulties inherent in the practices that as individuals we carry out in the public field of university academic management: how we deal with and create these institutionalised tasks and functions in order to include in them the necessary doses of reflective and critical thought. It is my concern to work from evaluation, from creative strategies leading to more communicative and democratic ways of management. It is important to reconsider this field politically and theoretically because we are immersed in Argentina’s public university, because it is necessary to preserve its symbolic value as an educational social institution and because academic matters as a group activity demands putting into practice specific skills.